Интегрирование процедуры создания и расчета схем ГТУ в САПР "Турбоагрегат" - Бойко, Анатолий Владимирович; Говорущенко, Юрий Николаевич; Усатый, Александр Павлович; Руденко, Алексей Сергеевич (НТУ "ХПИ", 2009)
Описані особливості інтегрування нових компонент до САПР "Турбоагрегат". Виконано інтегрування процедури створення та розрахунку схем ГТУ до САПР. Для перевірки працездатності зазначеної процедури проведені розрахунки та оптимізація параметрів циклу ГТ-750-6М. Наведені результати розрахунків та оптимізації.

Features of integration of new components to CAD «Turboaggregate» were described. Integration of procedure of creation and calculation of gas turbine installation diagram to CAD was executed. For procedure operation test the calculation and optimization of cycle parameters of GT-750-6М were performed. Results of calculations and optimization are resulted.
Integration of procedure of creation and calculation of gas turbine installation diagram to CAD "Turboaggregate"
Keywords: природные ресурсы; эффективность турбоустановок; оптимальное проектирование; интегральные параметры